Eskom's COVID-19 force majeure. Issue 3 (25th July 2020) - Ward, Michael
Abstract : Learning outcomes: The case describes the fall of Eskom, which in 2001 was named the Financial Times' Power Company of the Year, but by 2019 was suffering from "systemic corruption, malfeasance, fraud and state capture" that had "compromised the credibility of the organisation and eroded investor confidence". Eskom's incompetent management lays the ground for reasonable doubt as to whether the force majeure notice was indeed irresistible. The case suggests several methods available in financial markets to hedge risk – but to what extent are these relevant and appropriate? The main objective of the case, however, is to examine and assess the criteria required to claim force majeure. Two aspects are questionable: Was the virus unforeseeable and was it irresistible? Eskom is "bleeding" R 2 .5m per month because of significantly reduced electricity demand, and while it clearly benefits Eskom to break their supply contract, the consequences for Exxaro are far more dire. And, if carried to conclusion, how would such actions impact the entire economy? Case overview/synopsis: In April 2020 South Africa's stated-owned electricity utility Eskom sent a pre-cautionary force-majeure notification to Exxaro Limited's Grootegeluk Coal Mine. The notification, citing COVID-19 as an unforeseeable, external and irresistible event, would have disastrous consequences for the mine's 25 m tonnes pa coal contract to supply Eskom's Medupi power station. Not only was the legality of the force-majeure questionable, it was unethical, and not in the spirit of President Ramaposa's call to businesses to continue paying contractors. The case briefly describes Eskom's troubled history following South Africa's 1994 democratic election. It examines the force majeure clause common in contracts, and questions whether COVID-19 meets the criteria of an "unforeseeable, external and irresistible" event. Complexity academic level: MBA and Executive Education Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 7: Management Science.